Gender Construction in Southeast Asia Through a Social Constructivism Perspective - Ahnaf Fairuzuhdy Aslam; Erika Intan Hulieta; Ammar Bianda Katon (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2022)
The LGBTQ+ community often become a topic of discussion among the global community, including in Southeast Asia. Not only does attention gets support, praise, and criticism, and conflict also emerges in response to this phenomenon. The author raised this discourse to understand the reason for the response given by the community in several Southeast Asia countries. The author uses qualitative research using secondary data in analyzing. The authors will choose the Philippines, Indonesia, and Myanmar as study cases with the social constructivist theory approach. Because the three countries have different cases and levels of acceptance of the LGBTQ+ community. Therefore, the authors understand what is behind the community's views regarding the acceptance of the LGBTQ+ community in three countries in Southeast Asia. The results of this study indicate that the construction of gender in the three countries comes from diverse backgrounds, such as Indonesia, which is dominated by religious morals; the Philippines shaped by local culture; and Myanmar caused of the obstruction of the flow of discourse due to political instability as well as religious views in the country. Keywords: Gender Construction, Indonesia, LGBTQ+, Myanmar, Philippines Abstrak Komunitas LGBTQ+ sering menjadi sebuah pembicaraan hangat di kalangan masyarakat global, termasuk di Asia Tenggara. Tidak hanya perhatian yang didapat, dukungan; pujian; kritik; dan konflik juga muncul sebagai respons terhadap fenomena ini. Penulis mengangkat diskursus ini dengan tujuan memahami apa yang menjadi alasan dari respons yang diberikan oleh masyarakat di beberapa negara Asia Tenggara. Penulis menggunakan penelitian kualitatif dengan menggunakan data kepustakaan sekunder dalam menganalisis. Dengan pendekatan teori konstruktivis sosial dalam metode studi kasus negara Filipina, Indonesia, dan Myanmar, dengan alasan ketiga negara tersebut memiliki kasus dan tingkat penerimaan terhadap komunitas LGBTQ+ yang berbeda dengan satu sama lain. Penulis memahami apa yang melatarbelakangi pandangan masyarakat mengenai penerimaan komunitas LGBTQ+ di tiga negara di Asia Tenggara tersebut. Hasil dari penelitian ini menunjukkan bahwa konstruksi gender di ketiga negara tersebut berasal dari latar belakang yang beragam, seperti Indonesia yang didominasi diskursus berlandaskan moral agama; Filipina yang dibentuk oleh kebudayaan lokal; dan Myanmar yang disebabkan oleh terhambatnya arus diskursus akibat instabilitas politik sekaligus pandangan agama di negara tersebut. Kata - kata kunci: Filipina, Indonesia, Konstruksi Gender, LGBTQ+, Myanmar